Kinetics of haze formation in beer – turbidity and flavan-3-ols - Kusche, Marc; Geiger, Eberhard (BrewingScience, 2007)
Kinetics of haze formation were studied by observing the development of turbidity, the correlation between built aggregates and flavan-3-ols and the reduction of these polyphenols during storage of different stabilised beers at different temperatures. Sample preparation was done by solid phase extraction followed by a HPLC-DAD.Kinetics of haze formation was influenced by the amount of flavan-3-ols in fresh beer as well as by the storage temperature of bottled beer. Although turbidity showed the same measured value, the reactive amount of flavan-3-ols differed when the beer was stored at different temperatures.